الخطاب المسجدي ودوره الدعوي الشيخ متولي الشعراوي - أنموذجا - - بوترعة, ريمة; بوعافية, الصالحة; ليحيو, بشيرة; منصر, يسمينة (جامعة الوادي university of eloued, 2020)
جاءت الد ا رسة للتعمق في موضوع "الخطاب المسجدي ودوره الدعوي الشيخ متولي الشع ا روي أنموذجا " الشيخ المعروف بمحاض ا رته ودروسه وخطاباته المسجدية الدعوية القوية الهادفة قولاً وفعل ، والخطاب من أحد أبرز ما يقوم به الإمام والداعية في المسجد الذي هو مؤسسة دينية تربوية، وكتاب الشيخ خطب الجمعة والعيدين من أكثر الكتب الشاملة لخطاباته المسجدية العديدة، لذا قامت عليه الد ا رسة. وهدف موضوع د ا رستنا الخطاب القائم في المساجد والدور الذي يقوم به في إيصال الدعوة الإسلمية للمسلمين وغيرهم. وحددت الإشكالية بالصيغة التالية: ما هو الدور الدعوي الذي لعبه الشيخ الشع ا روي من خلل خطابه المسجدي؟ وقد بنيت الد ا رسة على المنهج الوصفي التحليلي، وأبرز النتائج التي توصل ت إليها هي: أكثر الوسائل تأثي ا رً في مشاعر السامعين والمبصرين في الخطابات المسجدية خطب الجمعة والعيدين. الخطاب المسجدي له دور فعال في نشر النصح والإرشاد واصلح الذات وتوعية العباد وتسوية الفكر من الظواهر المخلة بالمجتمع وتصفية الفساد. 6 Summary The study came to delve into the topic of the mosque discourse and its advocacy role, Sheikh Metwally Al Shaarawi as a model, the sheikh known for his lectures, lessons, and mosque speeches The strong advocacy that aims in word and deed, and the speech is one of the most prominent things that the preacher does in the mosque, which is an educational religious institution, and the Sheikh's book Friday sermons and the two holidays is one of the most comprehensive books of his many mosque speeches. The objective of the subject of our study is the existing discourse in mosques and the role it plays in delivering Friday and Eid sermons. Islamic call to Muslims and others. The problem was defined in the following form: What was the advocacy role that Sheikh Al Shaarawi played through his mosque speech? Has The study is based on the descriptive and analytical approach, and the most prominent results that it reached are - the most effective means on the feelings of the listeners and perceptions in the mosque speeches -The mosque discourse has an effective role in spreading advice and guidance, self-reform, educating people, settling thought from the disruptive phenomena of society and liquidating corruption.
دعوة